Quimlibras: objeto virtual de aprendizagem (ova) como instrumento de articulação entre a química e a libras/elis - (:unkn) unknown (Universidade Estadual de Goiás, 2018)
Quimlibras is a virtual learning object (OVA) that was created by a working group (WG) formed by three bilingual participants of the language pair Libras/Portuguese. Quimlibras is a learning tool that is broadly part of a field of research called Chemistry-Linguistic Studies, and more specifically, the link between Chemistry and Libras. The design and stages of the process had the active participation of three participants: two deaf and the bilingual chemistry teacher-researcher as members of the WG, as well as the contribution of four more deaf collaborators who were invited to evaluate educational products. The main theoretical references used for this research were: Santos and Barros (2016), Barros (2008, 2015), Saldanha (2011), Jonhstone (1993, 2010), Wu, Krajcik, Soloway, Souza and Silveira (2011) and Marques (2014). The methodology of the research was based on the qualitative research with focus on the case study of observation. The products elaborated were: 1. OVA-Quimlibras; 2. The glossary of Quimlibras; 3. The periodic table of ELiS visografemas; 4. Signal types and phonological description of the signs of the Quimlibras Glossary; 5. The tables with the signal language registers by means of the ELiS system with a total of 342 signals in which were divided 46 in Libras, 233 in ASL and 63 in BSL of chemical signals. GT-Quimlibras created 13 signs for the representation of chemical language in Libras at all three levels (macroscopic, microscopic and symbolic) for the OVA glossary.
Keywords: Ensino de Química em Libras; OVA; Quimlibras; Glossário; Escrita das Línguas de Sinais (ELiS); Teaching Chemistry in Libras; OVA; Quimlibras; Glossary; Sign Language Writing (ELiS); CIENCIAS EXATAS E DA TERRA::QUIMICA